Recuperación Paisajista De La Quebrada El Tejar A Partir De La Agricultura Urbana En Ibagué (2022)
Through the investigation, some environmental problems are observed due to the houses adjacent to the Tejar creek, which influence the deterioration of the quality of the water and the soil in the area related to the water round, specifically in the section that it crosses. commune 12, in addition to invading the isolation required by the municipal regulations for the protection of the environment.